The Relation between Epstein-Barr Virus and Hodgkin's Disease: lmmuno-histo- pathological Analysis of EBV LMP-1 expression) - C. Murtono C. Murtono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
EBV-LMP-1 is one of the proteins formed in the B lymphocytes and that has an oncogenic property and expressed by Sternberg Reeds cells. Detection of EBV LMP-1 is a reliable method to determine the presence of EBV in Hodgkin's disease. There were geographical distributions of Hodgkin's disease based on its histological classification. This study determined the correlation between EBV and Hodgkin's disease based on its histological subtype in Yogyakarta. Eighteen formaldehyde fixed in paraffin wax embedded specimen of Hodgkin's disease were investigated for their EBV-LMP-1 expression by immunohistochemistry reaction with cocktail CS 1-4 (DAKO) as monoclonal antibody and Mayer's Hematoxillin as counterstain. For negative control LMP-1 monoclonal antibody was omitted. EBV LMP-1 expression was detected in 9/18 (50%) of Hodgkin's disease cases. The frequency of Hodgkin's disease subtypes is as follows LP (lymphocytic predominance) 11.11%, NS (nodular sclerosis) 11.11%, MC (mixed cellularity) 22.22% and LD (lymphocytic depletion) 55.55%. The median age of the patients is 52.5 years with mean 52.3 year and SD 9.15 year. LMP-1 positivity was detected in 0/2 (0%) for LP subtype, 1/2 (50%) for NS, 2/4 (50%) for MC, and 6/10 for LD (60%). Based on EBV LMP-1 expression in the Sternberg Reed cells, it corroborated a significant role for EBV on the oncogenesis of Hodgkin's disease in Yogyakarta especially for LD subtypeKey Words : Hodgkin's disease - histological classification - latent membrane protein-1 (LMP-1) -immunohistochemistry - oncogenesis.